Ted [videorecording (DVD)] - MacFarlane, Seth, 1973-; Wahlberg, Mark, 1971-; Kunis, Mila, 1983-; McHale, Joel, 1971-; Ribisi, Giovanni, 1974-; Warburton, Patrick; Walsh, Matt, 1964- (Universal Home Video, 2012)
As the result of a childhood wish, John Bennett's teddy bear, Ted, came to life and has been by John's side ever since. Their friendship is tested when Lori, John's girlfriend of four years, wants more from their relationship.